SYNTHESIS AND CHARACTERIZATION HYDROXYAPATITE FROM CALCIUM OXIDE (CAO) CHICKEN EGG SHELL WITH PRECIPITATION METHOD - Siswoyo, Eko; Gunawan, . (MATTER: International Journal of Science and Technology, 2018)
Hydroxyapatite is a constituent compound of tissues in the body such as bones and teeth that can be synthesized from eggshells that have high calcium content. Hydroxyapatite is biocompatible so it can be used as a dental implant. The purpose of this research is to utilize eggshell waste to be synthesized into hydroxyapatite material as base material of dental implant. Hydroxyapatite was synthesized from eggshell nanoparticles calcium oxide (CaO) by mixing HCl, NH3 and Na3PO4 solutions using precipitation method. The synthesis was carried out by 4 samples with the molarity of Na3PO4 4 varied samples ie 4M, 5M, 6M and 7M then calcined at 750 ° C for 4 hours. The results of XRD characterization, showed that the highest Hydroxyapatite content was found in the addition of Na3PO4 5M ie 58 wt%. The crystalline morphology of SEM (Scanning Electron Microscopy) characterization shows that the hydroxyapatite sample has a regular structure and uniform crystal size, while the EDS analysis shows the most dominant CaO content with a grade of 55.91%.